Single‐nucleus RNA sequencing of plant tissues using a nanowell‐based system. (15th September 2021) - Sunaga‐Franze, Daniele Y.; Muino, Jose M.; Braeuning, Caroline; Xu, Xiaocai; Zong, Minglei; Smaczniak, Cezary; Yan, Wenhao; Fischer, Cornelius; Vidal, Ramon; Kliem, Magdalena; Kaufmann, Kerstin; Sauer, Sascha
SUMMARY: Single‐cell genomics provides unprecedented potential for research on plant development and environmental responses. Here, we introduce a generic procedure for plant nucleus isolation combined with nanowell‐based library preparation. Our method enables the transcriptome analysis of thousands of individual plant nuclei. It serves as an alternative to the use of protoplast isolation, which is currently a standard methodology for plant single‐cell genomics, although it can be challenging for some plant tissues. We show the applicability of our nucleus isolation method by using different plant materials from different species. The potential of our single‐nucleus RNA sequencing method is shown through the characterization of transcriptomes of seedlings and developing flowers from Arabidopsis thaliana . We evaluated the transcriptome dynamics during the early stages of anther development, identified stage‐specific activities of transcription factors regulating this process, and predicted potential target genes of these transcription factors. Our nucleus isolation procedure can be applied in different plant species and tissues, thus expanding the toolkit for plant single‐cell genomics experiments. Significance Statement: We introduce an optimized plant nucleus isolation procedure followed by single‐nucleus RNA sequencing that can be applied to different plant tissues. We exemplify the utility of this method by analyzing cellular heterogeneity in Arabidopsis seedlings and flowers.